Prognostic value of interleukin 2 and interleukin 15 in peritumoral hepatic tissues for patients with hepatitis B-related hepatocellular carcinoma after curative resection. Issue 12 (12th October 2010) - Zhou, Haijun; Huang, Hua; Shi, Jiong; Zhao, Yue; Dong, Qiongzhu; Jia, Huliang; Liu, Yinkun; Ye, Qinghai; Sun, Huichuan; Zhu, Xiaodong; Fu, Liyun; Guo, Kun; et al.
Abstract : Background and aims: Th1/Th2-like cytokine mRNA levels in non-cancerous hepatic tissues from patients with hepatocellular carcinoma (HCC) are associated with metastases and recurrence. This study evaluated the prognostic values of intratumoral and peritumoral Th1/Th2 cytokine protein levels in patients with HCC after curative resection. Methods: Two independent cohorts (A and B) of 453 patients with HCC were enrolled. Twelve Th1/Th2 cytokines in tumour and peritumoral hepatic tissues from cohort A (n=192) were quantified with enzyme-linked immunosorbent assays. This cohort was split into training and test sets which were used to identify and verify the prognostic cytokines. The prognostic values of identified cytokines were further validated in cohort B (n=261) using tissue microarray and immunohistochemical staining. Results: In the training set, higher interleukin (IL)-2 and IL-15 levels in peritumoral liver tissues, but not in tumour tissues, were significantly associated with a decreased incidence of recurrence of intrahepatic tumour and a prolonged overall survival. This association was verified in the testing set and further validated in patients in cohort B. Importantly, this correlation remained significant in patients with early HCC. Univariate and multivariate analyses indicated that the prognostic performance of peritumoral IL-2 (HR for recurrence=0.4, 95% CI 0.3 to 0.6, p<0.0001; HR for death=0.6, 95% CI 0.4 to 0.8, p=0.005) and IL-15 (HR for recurrence=0.7, 95% CI 0.5 to 0.95, p=0.025) was independent of other clinicopathological factors. Conclusion: Peritumoral IL-2 and IL-15 levels are useful for stratifying patients, even those with early-stage HCC, into subgroups with different prognoses after curative resection.